A review of the concepts of strategic communication and public management within the framework of participatory organizational processes - Mejía, Claudia Margarita; Navarro Díaz, Luis Ricardo (Corporación Universitaria Americana, 2016)
Este artículo analiza procesos de comunicacio?n estrate?gica en la construccio?n de identidad, cultura y participacio?n ciudadana, como pilares para asegurar la efectividad de la gestio?n pu?blica en la bu?squeda del cumplimiento de los objetivos y fines de las organizaciones. En este marco, se propone una revisio?n teo?rica que aborda el concepto de comunicacio?n estrate?gica en relacio?n con procesos de desarrollo de la gestio?n pu?blica de las organizaciones. El impacto del estudio, no solo se encuentra en la posibilidad de ser asumido como referente teo?rico para la toma de decisiones por parte de los li?deres de diversas organizaciones, sino en ofrecer reflexiones y procesos comunicativos pertinentes para realizar procesos de seguimiento y control por parte de los actores sociales pertenecientes a una organizacio?n. Palabras clave: Comunicacio?n estrate?gica, Gestio?n pu?blica, Organizacio?n, Participacio?n. ABSTRACT This article analyzes strategic communication processes in the construction of identity, culture and citizen participation, as pillars to ensure the effectiveness of public management in the search for compliance with the objectives and purposes of organizations. In this context, a theoretical review is proposed to analyze the concept of strategic communication and its relationship with the processes of public management of organizations. The impact of the study is not only in the possibility of being assumed as a theoretical reference for decision making by the leaders of public organizations, but also to offer relevant reflections from the strategic communication to execute follow-up processes, observation citizen and public control by social actors belonging to public management. Keywords: Strategic communication, Public management, Organization, Participation.